COMPARISON OF EFFICACY OF CHLOROQUINE AND ARTEMETHER/LUMAFANTRINE IN TREATING VIVAX MALARIA IN THALL AND SURROUNDING AREA - Abrar, Syed Mohammad; Shah, Syed Sajid Ali; Akbar, Raja Jibran; Rahim, Sheema; Malik, Faizan; Khan, Fakhar Uz Zaman (Journal of Ayub Medical College Abbottabad, 2017)
Background: Fever is the main complaint in patients reporting to our hospital and the most common cause of fever in our set up is malaria. The aim of this study was to know about the clinical response, efficacy and resistance of vivax malaria to chloroquine in patients reporting to Thall Scouts Hospital. Methods: All the adult male patients reporting to Thall scouts hospital with fever and other symptoms of malaria having slide positive vivax malaria were included in the study. Both thick and thin slide were used for the diagnosis and species determination of malaria. Age group of the patients was from 18-40 years old. The study was conducted for the period of two years. Results: Total number of patients included in the study was 518. Of the 518 patients, 374 (72.2%) responded to chloroquine and the remaining 144 (27.8%) were given Arthemether/Lumafantrine combination. Having positive symptoms of malaria total 374 patients treated with chloroquine 171 (45.72%) were asymptomatic after 24 hours, 98 (26.2%) after 48 hours, 78 (20.86%), after 72 hours of treatment while 27 (7.22%) were found to be resistant to chloroquine. Of the 144 patients having positive malaria treated with Artemether/Lumafantrine 62 (43.06%) were asymptomatic after 24 hours, 65 (45.14%) after 48 hours, 13 (9.03%) after 72 hours while 4 (2.78%) had still positive symptoms of malaria. Conclusion: Vivax malaria in our set up is sensitive to both Chloroquine and Arthemether/Lumafantrine. As Chloroquine is a cheap and easily available drug, so it can be safely given to patients with vivax malaria. It will also decrease the total cost of the disease. Keywords: Malaria; Vivax; Chloroquine; Artemether; Plasmodium